Methods for treating bipolar mood disorder associated with markers on chromosomes 18p - Freimer, Nelson Bruce (1997)
The present invention is directed to methods of detecting the presence of a bipolar mood disorder susceptibility locus in an individual, comprising analyzing a sample of DNA for the presence of a DNA polymorphism on the short arm of chromosome 18 between the telomere and D18S481, wherein the DNA polymorphism is associated with a form of bipolar mood disorder. The invention for the first time provides strong evidence of a susceptibility gene for bipolar mood disorder that is located in the terminal 5 cM region of the short arm of chromosome 18. The disclosure describes the use of linkage analysis and genetic markers in this 5 cM region to fine map the region and the use of genetic markers to genetically diagnose (genotype) bipolar mood disorder in individuals, to confirm phenotypic diagnoses of bipolar mood disorder, to determine appropriate treatments for patients with particular genotypic subtypes. Isolated polynucleotides useful for genetic linkage analysis of BP-I and methods for obtaining such isolated polynucleotides are also described.